Financial Report Ratio Analysis at PT. Gudang Garam Tbk Period 2019-2023 - Awal Ramadhan Purba; Desmi Manurung; Randa Wijaya; M. Fais Rizky (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of the study was to determine the financial performance of PT. Gudang Garam Tbk for the period 2019-2023. The inquire about strategy employments graphic inquire about with a quantitative approach . The data source used was obtained from www.idx.co.id and the data required is the Annual Financial Report of PT. Gudang Garam Tbk listed on the Indonesia Stock Exchange (IDX). Data collection techniques are documentation and literature studies. Data analysis techniques are financial ratios consisting of liquidity, solvency and profitability ratios. The results of the study indicate that financial performance reviewed from the perspective of the liquidity ratio for the period 2019-2023 as measured by the current ratio shows good results, while the quick ratio and cash ratio show poor results. The solvency ratio for the period 2019-2023 as measured by the debt to total assets ratio and the debt to equity ratio shows poor results. The profitability ratio for the period 2019-2023 as measured by the Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Investment (ROI), and Return On Equity (ROE) shows poor results